Adhesion of Insect Cells Expressing the Feline Herpesvirus Type 1 Hemagglutinin (gD) to Feline Cell Lines - MAEDA, Ken; ONO, Mitsuru; KAWAGUCHI, Yasushi; OKAZAKI, Katsunori; YOKOYAMA, Naoaki; TOHYA, Yukinobu; MIKAMI, Takeshi (Journal of Veterinary Medical Science, 1997)
Feline herpesvirus type 1 (FHV-1) gD-expressing Sf9 cells adhered to two feline cell lines, but not to the porcine, bovine, or canine cell lines tested. In addition, this adhesion activity was inhibited by a monoclonal antibody against FHV-1 gD. These results showed that the FHV-1 gD might bind to a specific-molecule(s) on the surface of feline cell lines. We discussed a possible importance of the FHV-1 gD in host cell restriction to FHV-1 infection.